Origins of racial supremacism, and the twilight of other races (Encuentros, 2020)
The article is a reflection based on theoretical foundations on the evolution of society, the economy, and culture. In every historical period of the human being there are the traces that he has left of racial imposition. It was evident in the groups of trivial bands, in Greek civilizations, in the conquest and reconquest of indigenous people, and in the slave trade, the latter physically and culturally annihilated with the flags of Christianity. As cultures have also evolved, dominance and the idea of superiority have had their cruelties and complexities especially in colonial times. Currently the practices of cultural and racial imposition are made with more savagery.